ILMU DALAM PERSPEKTIF FILSAFAT (Suatu Upaya Mengembalikan Ilmu pada Hakikatnya) - Wilujeng, Sri Rahayu (HUMANIKA, 2014)
Science is a subsidiary of philosophy. As a mother, philosophy has a responsibility to guard science in order to keep on the right track. Science building is on three philosophical foundation: ontological, epistemological and ethicl grounding. They are all important, no one can be abandoned. Science should not only highlight one these aspect. Nowdays science developes to become many branchs. Each branch tends to emphasize one aspect of some elements of science. The condition is more complicated when many interests get involved. Science must remember its duty and mission. Any sophisticated development of a science, should not leave its philosophical foundation, so that science does not come out of its essence, which is to be able to contribute to the life of mankind.